THE USE OF BUDGETARY AND FINANCIAL INFORMATION BY POLITICIANS IN PORTUGAL: - Jesus, M.; Jorge, S.M. (15th Biennial CIGAR Conference, 2015)
After more than thirty years of reforms in public sector accounting, marked by approximation to the business accounting model, namely through the introduction of accrual-based financial accounting, the usefulness of the information produced by public sector accounting systems worldwide seems to be questioned. Considering the main purposes of accountability and decision-making, questions raise especially concerning the use and usefulness by those considered one of the main users of the public sector budgetary and financial information – politicians. The debate in the academic sphere not only discusses whether politicians use budgetary and financial reporting information, but also why they do not use, if this is the case. Some seem to believe that information technicality and complexity might be one of the reasons limiting its use by politicians. Therefore, it appears that advisory and supporting technical groups – ‘information brokers’ – play an important role as intermediaries in treating and simplifying budgetary and accounting information to be used by politicians. This paper aims at analysing the type of information, as well as its use and usefulness, by politicians either members of parliament or members of central government in Portugal, through the analysis of the intermediary role of advisory and supporting technical bodies, such as CFP, UTAO and DGO. Main findings allow concluding that, although there seems to be a general acknowledgement of the split cash-based/accrual-based budgetary and financial information, both technical units and politicians in Central Government in Portugal give privilege to cash-based budgetary information for their use to support political debates and policy-making. Technical advisory and supporting units, especially DGO and UTAO, have a crucial role in gathering and preparing the information for politicians, i.e., the use of public sector budgetary and financial information by politicians would not be the same without these units’ expertise. However, they also prefer and rely on cash-based information, especially for budgetary reporting purposes. Maybe because the members of these units are economists and not accountants, accrual-based (financial) accounting is misunderstood with ESA and the National Statistics. Additionally, both technical units and politicians associate financial information needs to National Accounts purposes, mainly to assess deficit and debt accomplishment under Maastricht criteria. In summary, although it is obvious that the work of the technical advisory or supporting units has great contribution for the use of public sector budgetary and financial information by politicians, it seems also clear that these units probably need members with accounting expertise, so as accrual-based financial information might be gathered and analysed in order to be understood and used by politicians. While being an explorative study, this paper is original as an unprecedented research, contributing to both clarify on the use of budgetary and financial information by politicians, as well as on highlighting the role of intermediaries as experts that might affect the use and usefulness politicians consider regarding that type of information.